Workshop for Key Staff of Geriatric Education Centers (4th, Houston, Texas, April 21-24, 1988). Workshop Report - Texas Consortium of Geriatric Education Centers, Houston; Texas Consortium of Geriatric Education Centers, Houston ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
This document contains an executive summary and the report of the workshop. An overview highlights major events and outcomes of the workshop. Major addresses and the staff development sessions that occurred at a workshop for key staff of geriatric education centers (GECs) are discussed. Summaries of presentations include the following: "Welcome, Introductions, and Review of Purposes" (Roush, Gleich); "Federal Perspective of National GEC Program" (Louden, Gleich); "Management of Geriatric Education Centers" (Louden, Koenig, Gleich); "Program Development" (Saunders, Feather, Teitelman); "Evaluation Strategies" (Karuza, Hubbard, Torian); "Models in Geriatric Education: Impressions and Concerns" (Prothero, Groth, Sanchez); "Strategies to Promote Education in Geriatrics" (Connelly, Parlak, Nelson); "Accessing Educational Resources" (Davis, Mellor, Gardner); "Establishing Community Linkages" (Marshall, Noback, Tryon); "Relationship of Geriatric Education to Service Delivery Models" (Abrass, panel discussion--Hughes, Dimond, Luchi); "Linkage Binding; Evaluation; Curriculum; Issues and Trends" (Saunders et al.); Discussion of Transition of Task Forces to Work Groups; "Issues in Geriatric Education" (Hatch, panel discussion--Besdine, Dobrof, Pfeiffer); GEC Staff Development Sessions and Group Reports to Plenary Sessions; "The Role of GECs in Community Development" (panel discussion--Brasfield, Haber, Rankin, Oppenheimer); "Future Directions for Geriatric Education Centers" (panel discussion--Calkins, Beck, Kowal, Fulmer). A list of participants' names and addresses is included. (KC)
Sponsoring Agency: Health Resources and Services Administration (DHHS/PHS), Rockville, MD. Bureau of Health Professions.
Contract Number: HRSA-240-87-0071.
Educational level discussed: Postsecondary Education.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Aging (Individuals); Delivery Systems; Educational Gerontology; Federal Programs; Geriatrics; Postsecondary Education; Program Administration; Program Development; Staff Development; Geriatric Education Centers; Collected Works, Proceedings; Reports, Descriptive